Microvessel Density Lebih Tinggi pada Subtipe Non-GCB Diffuse Large B Cell Lymphoma - Wisnu Murti Suradilaya (Majalah Patologi Indonesia, 2026)
Background Diffuse large B cell lymphoma (DLBCL) is the most common type of non-Hodgkin's lymphoma. Based on cell of origin, DLBCL divided into 2 subtypes; germinal center B-cell-like (GCB) and non-germinal center B-cell-like (non-GCB). Tumor microenvironment (TME) plays an important role in stimulating angiogenesis and can be assessed by calculating microvessel density (MVD). Moreover, MVD is one of the most useful prognostic markers for monitoring progression and patients’ survival of malignancies. This study purpose was to determine the correlation between DLBCL subtypes with MVD. Methods An observational analytic study with a cross-sectional design was performed at the Anatomic Pathology Department, Medical Faculty, Sriwijaya University/Dr. Mohammad Hoesin Hospital Palembang. Purposive sampling was conducted to achieve the same proportion of GCB and non-GCB subtypes. Thirty blocks of patients diagnosed with DLBCL for the period 2017 – 2021 with complete clinicohistopathological data were attained from archive. Slides were immunostained with an anti-CD34 antibody, followed by the MVD identification by observing the morphology of stained endothelial cells, then photographed, and counted with Image J software. Data were analyzed statistically with SPSS version 26. Results DLBCL was diagnosed more in older patients (<60 years, 66,7%), male (60%), nodal location (53,3%), and centroblastic variant (93,3%). The distribution of high MVD tends to be higher in older patients, male, at nodal location, with centroblastic morphological variants. Although the MVDs of the DLBCL subtypes were not significantly different, a higher trend of MVD was noticed in the non-GCB subtypes. Conclusion Higher microvessel density was observed in the non-GCB molecular subtype.